Sarcopenia and piscines: the case for indeterminate-growing fish as unique genetic model organisms in aging and longevity research - Froehlich, Jacob M.; Fowler, Zachary; Galt, Nicholas J.; Smith, Daniel L.; Biga, Peggy R. (Frontiers in Genetics, 2013)
Sarcopenia and dynapenia pose significant problems for the aged, especially as life expectancy rises in developed countries. Current therapies are marginally efficacious at best, and barriers to breakthroughs in treatment may result from currently employed model organisms. Here, we argue that the use of indeterminate-growing teleost fish in skeletal muscle aging research may lead to therapeutic advancements not possible with current mammalian models. Evidence from a comparative approach utilizing the subfamily Danioninae suggests that the indeterminate growth paradigm of many teleosts arises from adult muscle stem cells with greater proliferative capacity, even in spite of smaller progenitor populations. We hypothesize that paired-box transcription factors, Pax3/7, are involved with this enhanced self-renewal and that prolonged expression of these factors may allow some fish species to escape, or at least forestall, sarcopenia/dynapenia. Future research efforts should focus on the experimental validation of these genes as key factors in indeterminate growth, both in the context of muscle stem cell proliferation and in prevention of skeletal muscle senescence.